Tramadol can selectively manage moderate pain in children following European advice limiting codeine use. - Marzuillo, Pierluigi; Calligaris, Lorenzo; Barbi, Egidio (Acta Paediatr, 2014)
UNLABELLED: The European Medicine Agency recommendations limiting codeine use in children have created a void in managing moderate pain. We review the evidence on the pharmacokinetic, pharmacodynamic and safety profile of tramadol, a possible substitute for codeine. CONCLUSION: Tramadol appears to be safe in both paediatric inpatients and outpatients. It may be appropriate to limit the current use of tramadol to monitored settings in children with risk factors for respiratory depression, subject to further safety evidence.